Perception, experiences and attitudes on gender discrimination in the labour market in Croatia - some sociological aspects - Galić, Branka, sociolog (2011)
In the year 2009. in Croatia was carried out an interdisciplinary research on perceptions, experiences and attitudes about gender discrimination in fields of family, education, labor market and politics. In this paper are presented some results of that research about gender discrimination in the labor market in Croatia. The survey was conducted on a representative sample of 1363 citizens (648 men and 715 women), from 15-89 years old. We assumed that respondents will show some differences in perception, attitudes and experiences concerning gender discrimination in the labor market due to their different socio-demographic characteristics (sex/gender, age, education, rural or urban areas and regional differences). The overall objective of the research was to determine perceptions, experiences and attitudes about gender discrimination against women and men in Croatia, as well as frequency and some possible forms of suppression in practice. The results showed a greater tendency towards gender discrimination against women in business and professional spheres, especially when it comes to better-paid jobs and the expectations of collegial cooperation of the male gender groups. Women showed a higher level of awareness and greater sensitivity to some forms of unequal gender treatment and/or discrimination against them in the labor market, than men did. Attitudes about gender in/equality in the labour market have confirmed just a general declaratory commitment to gender equality, also showed in other researches on sexism and the labor market in Croatia, too. However, when claims were concretized, results showed statistically significant differences in attitudes between women and men, while women were more willing to support more egalitarian gender relations in the labor market than men were.